Tinjauan Tokoh Al Washliyah dan Muhammadiyah Terhadap Tradisi Midodareni dalam Perkawinan Adat Jawa: Studi Kasus Kota Medan - Bima Arya Wardhana; Amal Hayati (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
In Javanese tradition, marriage is inseparable from a series of customary ceremonies. One such tradition is Midodareni, a ritual series performed on the eve of the wedding day, in which the bride-to-be is spiritually and mentally prepared to enter married life. This tradition is also practiced by the Javanese community in Medan City, including rituals such as Nemokkan Manten, Kembar Mayang, Pecah Telur, and Tepung Tawar. The Midodareni tradition receives differing views from two Islamic organizations in Medan City: Al Washliyah and Muhammadiyah. This study aims to examine the Midodareni procession, the perspectives of Al Washliyah and Muhammadiyah leaders in Medan regarding this tradition, and the differences in their views. This research employs an empirical sociological method with a comparative approach. The type of research used is field research, descriptive in nature, and utilizes a qualitative approach that seeks to portray phenomena as they occur in the field. The findings indicate that Al Washliyah leaders tend to adopt a moderate and accommodative stance, viewing the tradition as acceptable as long as it does not involve elements of shirk (polytheism) or contradict Islamic principles. They advocate for reinterpretation and adaptation of traditional meanings to align with Islamic values. In contrast, Muhammadiyah leaders perceive Midodareni as a cultural practice imbued with mysticism and symbolism lacking any foundation in Islamic teachings. Therefore, they reject its practice and call for the purification of marriage rites based solely on the Prophet’s Sunnah, excluding customary rituals.